1996
DOI: 10.1002/(sici)1097-4652(199609)168:3<638::aid-jcp16>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CD44 and the cytoskeletal linker protein ankyrin in human neutrophil bacterial phagocytosis

Abstract: The leukocyte CD44 and CD45 cell surface receptors are associated via the linker proteins ankyrin and fodrin with the cytoskeleton, which itself is important in immune cell functions such as adherence, chemotaxis, and phagocytosis. The effects of rat antihuman CD44 and CD45 monoclonal antibodies on phagocytosis of fluoresceinated heat-killed Staphylococcus aureus 502A by normal human neutrophils (PMNs) during 2 hr incubation in RPMI-1640 was studied via flow cytometry and confocal microscopy. Flow cytometry wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Redistribution of PAK1 to the cytoskeleton in response to cell surface receptor activation is inhibited by wortmannin and cytochalasin D Wortmannin and cytochalasin D have both been reported to modulate the functional responses of leukocytes through effects on the actin cytoskeleton [12,[34][35][36]. We observed that 10 µM cytochalasin D, a potent inhibitor of actin polymerization, added to neutrophils 10 min before stimulation with fMLP blocked cell polarization and the incorporation of F-actin into cell surface extensions.…”
Section: Pak1 Localizes To Pseudopodia and Phagocytic Cups During Phamentioning
confidence: 59%
See 1 more Smart Citation
“…Redistribution of PAK1 to the cytoskeleton in response to cell surface receptor activation is inhibited by wortmannin and cytochalasin D Wortmannin and cytochalasin D have both been reported to modulate the functional responses of leukocytes through effects on the actin cytoskeleton [12,[34][35][36]. We observed that 10 µM cytochalasin D, a potent inhibitor of actin polymerization, added to neutrophils 10 min before stimulation with fMLP blocked cell polarization and the incorporation of F-actin into cell surface extensions.…”
Section: Pak1 Localizes To Pseudopodia and Phagocytic Cups During Phamentioning
confidence: 59%
“…The PI 3-kinase inhibitor wortmannin blocks chemotactic peptide-induced development of cell polarity, increases in cytoskeletal actin, and phagocytosis in human neutrophils [8,10,12,[34][35][36][37][38]41]. We examined the effect of nanomolar (i.e., PI 3-kinase-specific) concentrations of wortmannin on PAK1 localization.…”
Section: Discussionmentioning
confidence: 99%
“…Both CD44 and RHAMM associate with the cytoskeleton [81,82], control tumor cell invasiveness, and transduce signals involved in proliferation, locomotion, focal adhesion turnover [83,84], indicating that both receptors may be responsible for hyaluronan traction. CD44 has been demonstrated to mediate phagocytosis [85,86], bringing up the idea that hyaluronan in the pericellular matrix may by used by cells to draw in other matrix components, cellular debris or other particles, thus facilitating phagocytosis. The full role of cellular traction on hyaluronan organization is not yet clear.…”
Section: Pericellular Matrix Regulation Of Cell Adhesionmentioning
confidence: 99%
“…CD44 has a large number of isoforms generated by alternative RNA splicing (10). The most common standard isoform is highly expressed on neutrophils (11). The glycosaminoglycan disaccharide hyaluronan (HA) is the main ligand of CD44, although other extracellular matrix proteins seem also able to interact with CD44 (10).…”
mentioning
confidence: 99%